Analyzing Powers It11 and T20 of Dp -> Ppn Reaction at 400 Mev Investigated at Nuclotron - Marian Janek; Vladimir P. Ladygin; Semen M. Piyadin; Yuri V. Gurchin; Alexander Yu. Isupov; Julia-Tatiana Karachuk; Anatoly N. Khrenov; Pavel K. Kurilkin; Alexei N. Livanov; Sergei G. Reznikov; Yaroslav T. Skhomenko; Gabriela Tarjanyiova; et al. (Communications - Scientific letters of the University of Zilina, 2017)
One of the tools to study spin structure of short range correlations (SRCs) and three nucleon forces is the measurement of the polarization observables. Deuteron induced reactions at intermediate energies are investigated at Internal Target Station (ITS) of Nuclotron through the dp elastic and dp → ppn reactions. Analyzing powers iT11 and T20 analyzing powers of dp → ppn reaction at 400 MeV are presented.